AN ASSESSMENT OF NON-OIL TAXATION INFLOW ON ECONOMIC GROWTH: VERDICT FROM WEST AFRICAN COUNTRIES - ADEGBITE, Tajudeen A. (Annals of Spiru Haret University. Economic Series, 2020)
This study examined the impact of non-oil taxation inflow on economic growth in selected West African countries using World Bank panel data from 1999 to 2018. Ten (10) West African countries were purposefully selected from 1999 to 2018. Specifically, five francophone and Anglophone countries were selected for this study. Panel data analysis was employed to articulate the effect of independent variables (company income tax, Value added tax, Education tax, and Custom and excise duties.) inflow on dependent variable (economic growth (GDP)). The results showed that corporate income tax, Value added tax, Education tax and Custom and excise duties had positive significant effect on economic growth of West African countries. In conclusion, non-oil taxation Inflow impacted economic growth significantly and positively in selected West African countries. This predicated that money realized as taxation income has been utilized effectively, productively and efficiently on economic enhancement in terms of employment creation, roads construction, income distribution, provision of infrastructural facilities and economic stability. This study postulated that West African countries should lay mush emphasis on the collection of non-oil taxation effectively especially VAT and CIT, and expend much of this revenue prudently for the augmentation and enrichment of the populace.